Lévinas, Blanchot, Jabès : figures of estrangement - Mole, Gary D. (Crosscurrents (Gainesville, Fla.), 1997)
In the first critical study to consider together the work of Emmanuel Levinas, Maurice Blanchot, and Edmond Jabes, Gary D. Mole demonstrates and compares the ways in which these writers have been instrumental in raising those issues of Jewishness that have been so central to contemporary postmodern thought. Judicious close readings and an accessible style help to render the work of these important thinkers intelligible to the specialist and nonspecialist reader alike while clearly situating them in their postmodern context and revealing their tremendous influence on a generation of philosophers and writers.